License Plate Recognition Using Undecimated Wavelet Transform - G. Kannan (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
License Plate Recognition (LPR) is the mission of identifying the vehicle using number plate extraction. An efficient method for recognizing plate based on Undecimated Wavelet Transform (UWT) is proposed. Plates are recognized using features from undecimated coefficients in this system. Morphological edge detection technique is used to get accurate results after feature extraction. Finally detected images are used for classification purpose using the feature coefficients. This technique is applied to all the unidentified and training images, extracted features are used as input to Back Propagation Neural Network (BPNN). The evaluation of the system is based on public database.